Association of Serum Uric Acid level in Patients with Alzheimer’s Disease - Ahtesam, Mohammad Saifullah; Habib, Md Ahsan; Islam, Md Rafiqul; Khan, Md Rezaul Karim; Rahman, Hasan Zahidur; Rizvi, Abu Nasir; Bhuiyan, Md Moniruzzaman; Barman, Kanuj Kumar; Showkat, Syeeda; Islam, Md Monirul; et al. (Bangladesh Journal of Neuroscience, 2017)
Background: Alzheimer’s disease is the most common cause of dementia. Uric acid is the end product of purine metabolism in humans and acts as a natural antioxidant, accounting up to 60% of the free radical scavenging activity in human blood to prevent free radicals induced oxidative cell injury. This study aimed to explore the association between serum uric acid level and cognitive impairment of Alzheimer’s disease patients compared to those of the non-demented age and sex matched controls. Methods: This case control study was carried out in the department of neurology, BSMMU, Dhaka. Total 116 patients were enrolled as study population after satisfying inclusion and exclusion criteria. Among them, 58 were grouped as case and rest 58 were control. All blood samples for serum uric acid were measured in the Biochemistry lab, Department of Biochemistry, BSMMU, Dhaka. Results: A signiûcant reduction of serum uric acid levels in the AD group was found compared to those of the control group (4.35±1.59 Vs 6.89±1.68) which was statistically significant (p<0.001). We also found a positive correlation between serum uric acid levels with severity of Alzheimer’s disease (rp = 0.633, P<0.001). Among demographic variables educational qualification was statistically significant (p=0.006) in AD patients. Conclusion: This study showed that oxidative injuries have an important role in the pathogenesis of AD. Higher levels of uric acid are associated with a decreased risk of dementia and better cognitive function later in life. Bangladesh Journal of Neuroscience 2017; Vol. 33 (2): 83-88